Synthesis, Bioactivity Screening and in silico Studies of Phenyl Thiazole Derivatives Containing Arylidene Moieties - Sultana, Sadia; Barua, Priya; Islam, Md. Din; Sutradhar, Ranajit Kumar (Asian Journal of Chemistry, 2025)
Thiazole, a heterocyclic compound containing Schiff bases being a compound’s core can enhance the drug potency. This study contributes to the synthesis of three novel thiazole Schiff base derivatives 2a-c by two-step synthesis method. The structures of the synthesized compounds were established by spectral analysis. Antimicrobial and antioxidant screening of synthesized compounds showed moderate to significant antimicrobial and antioxidant activities. Compounds 2c showed excellent antimicrobial and antioxidant activities. The synthesized analogs showed good binding affinity and a variety of strong interactions with the effective binding sites of the target receptors. In silico studies support the antimicrobial results very well. It is expected that the synthesized analogs have a good drug score and contribute to the development of a more potent drug in the future.